Penerapan Variasi Latihan dalam Peningkatan Pukulan yang Efektif Pada Siswa Perguruan Pencak Silat PSHT SMP Negeri 2 Lubuklinggau - Supriyadi, Muhammad; Ihsan, Nurul; Yendrizal, Yendrizal (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine the effect of technique on the effective striking ability of PSHT Extracurricular Pencak Silat College Students at SMP Negeri 2 Lubuklinggau in 2024. The research method uses a quasi-experimental method (pre-test and post-test group). This sample was all Pencak Silat extracurricular students at PSHT SMP Negeri 2 Lubuklinggau, totaling 20 athletes. Data collection techniques use test techniques. The data analysis technique uses the t test with the descriptive t test method. The results of this study stated that training (push-up training, skipping training, weight training) had a significant influence on the effective punching ability of extracurricular Pencak Silat PSHT students at SMP Negeri 2 Lubuklinggau with pre-test punch results of 1,270 and final test punches. (post test) 1.345 with comparison results of tcount 9.566 and ttable 1.734 (tcount > ttable). The conclusion of this research is that training has a significant effect on the effective striking ability of pencak silat students at the PSHT extracurricular pencak silat school at SMP Negeri 2 Lubuklinggau. Keywords : Effective Pencak Silat hitting; push-up exercise, skipping exercise, weight training,